THEORETICAL FOUNDATIONS FOR IMPROVING THE QUALITY OF BANK CREDIT PORTFOLIOS IN UZBEKISTAN (Symposium on Natural and Applied Sciences, 2026)
In modern conditions, the stability and sustainable development of the banking system of Uzbekistan largely depend on the quality of commercial banks’ credit portfolios. Since the credit portfolio constitutes the major share of bank assets, its efficiency directly affects the overall financial condition and risk exposure of banks. In recent years, a significant expansion in lending activities has been observed in the national banking system. According to data from the Central Bank of Uzbekistan, the total volume of commercial banks’ credit portfolios has exceeded 600 trillion UZS, which further increases the relevance of effective credit risk management and improvement of portfolio quality [1].